2015
DOI: 10.1038/srep12714
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide hydroxymethylcytosine pattern changes in response to oxidative stress

Abstract: The TET enzymes convert methylcytosine to the newly discovered base hydroxymethylcytosine. While recent reports suggest that TETs may play a role in response to oxidative stress, this role remains uncertain, and results lack in vivo models. Here we show a global decrease of hydroxymethylcytosine in cells treated with buthionine sulfoximine, and in mice depleted for the major antioxidant enzymes GPx1 and 2. Furthermore, genome-wide profiling revealed differentially hydroxymethylated regions in coding genes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“…The ten-eleven translocation (TET) family of genes hydroxylate methylated cystosines in a series of reactions that end with the base-excision repair (BER) machinery removing a 5′-formyl/carboxycystosine, generating a standard, unmethylated cytosine (Kohli and Zhang, 2013). This family of genes, while its precise role remains unclear, has been implicated in the cellular response to oxidative stress (Delatte et al, 2015). During bovine preimplantation development, the TET family of genes are thought to play a role in active genomic demethylation and resetting of the epigenome (Gu et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ten-eleven translocation (TET) family of genes hydroxylate methylated cystosines in a series of reactions that end with the base-excision repair (BER) machinery removing a 5′-formyl/carboxycystosine, generating a standard, unmethylated cytosine (Kohli and Zhang, 2013). This family of genes, while its precise role remains unclear, has been implicated in the cellular response to oxidative stress (Delatte et al, 2015). During bovine preimplantation development, the TET family of genes are thought to play a role in active genomic demethylation and resetting of the epigenome (Gu et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…However, embryo handling and best in vitro practices still necessitate transient exposures to atmospheric (20%) oxygen. Recently, a link between components of the oxidative stress pathways and enzymes controlling chromatin structure has been identified (Wang et al, 2011; Delatte et al, 2015). To gain a better understanding of the potential impact of oxygen exposures during in vitro embryo culture on the regulation of chromatin structure, we evaluated the capacity of differing oxygen concentrations to effect the transcriptional control of chromatin modifying genes and the regulation of imprinted gene expression, which previous studies have identified as being sensitive to embryo culture (de Waal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This observation was not limited to tumours and hypoxia, since also in endothelial cells, H 2 O 2 or hypoxia were shown to decrease TET activity and 5hmC base content (Niu et al , ; Sun et al , ) while DNMT3A, DNMT1 and 5mC levels were increased (Kalani et al , ) (Figure ). In support, 5hmC levels were decreased in kidneys exposed to ischaemia/reperfusion (Huang et al , ) and in patients with preeclampsia and gestational diabetes mellitus (Sun et al , ) while in mice with combined knockout of the antioxidant enzymes GPX1, and −2 (Delatte et al , ), 5hmC levels were increased. Interestingly, in human atherosclerosis and in a mouse model of vascular injury, not only the 5hmC content but also the TET2 expression were reduced, which both contributed to a switch of vascular smooth muscle cells from a contractile to a proliferative phenotype (Liu et al , ).…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 97%
“…Interestingly, a recent work also showed that oxidative stress could influence 5hmC enrichment and that many differential 5hmC-enriched regions (DHMRs) were located in genes associated with the gene ontology term of ''renal ischemia reperfusion''. 23 Since 5hmC is one of the oxidative derivatives of 5mC, it will be of great interest to investigate whether 5mC and other 5mC oxidative derivatives such as 5fC and 5caC could be used as epigenetic marks of IR injury-associated genes.…”
Section: Discussionmentioning
confidence: 99%